A Systematic Review and Meta-analysis of the Clinical Impact of Prophylactic Quinolones with Adjuvant Bacillus Calmette-Guérin Instillation for Non-muscle-invasive Bladder Cancer - Wong, Chris Ho-Ming; Ko, Ivan Ching-Ho; Leung, David Ka-Wai; Yuen, Steffi Kar-Kei; Siu, Brian; Yuan, Yuhong; Birtle, Alison; Capoun, Otakar; Compérat, Eva; Domínguez-Escrig, José L; Liedberg, Fredrik; Mariappan, Paramananthan; et al. (European urology oncology, 2025)
BACKGROUND AND OBJECTIVE: Bacillus Calmette-Guérin (BCG) reduces disease recurrence and progression in intermediate- and high-risk non-muscle-invasive bladder cancer (NMIBC). BCG-associated adverse events during instillations are common, leading to treatment cessation. Prophylactic use of quinolones in conjunction with BCG instillations is one approach for reducing BCG-associated adverse events. Our aim was to delineate the clinical impact of quinolone prophylaxis (QP) in patients receiving adjuvant BCG instillations for NMIBC. METHODS: In October 2024, a systematic search of MEDLINE, Embase, and the Cochrane Central Register of controlled trials was performed. Prospective and retrospective studies reporting comparative outcomes for patients with and without QP during BCG instillations were included. Outcomes were reported in a binary fashion. Random-effects meta-analysis using the weighted mean difference was conducted. Primary outcomes for pooled analyses included BCG-associated toxicities, the completion rate for BCG induction, the likelihood of antituberculosis treatment, and disease recurrence and progression at 12 mo. KEY FINDINGS AND LIMITATIONS: The systematic review included five studies. Four randomised controlled trials were included in the meta-analysis, and one nonrandomised study was also included in the narrative review. The studies involved 445 patients, of whom 194 received QP + BCG and 251 received BCG alone. QP use was associated with lower incidence of class ≥2 (40.8% vs 54.7%; relative risk [RR] 0.79, 95% confidence interval [CI] 0.67-0.94; p = 0.006), and class ≥3 BCG-associated toxicities (25.3% vs 36.4%; RR 0.70, 95% CI 0.50-0.98; p = 0.04) and a higher completion rate for BCG induction (83.0% vs 70.6%; RR 1.16, 95% CI 1.01-1.34; p = 0.04). The 12-mo recurrence rates (14.7% vs 19.4%; RR 0.76, 95% CI 0.46-1.27; p = 0.3) and progression rates (4.5% vs 6.4%; RR 0.86, 95% CI 0.09-8.25; p = 0.9) did not significantly differ for QP + BCG versus BCG alone. CONCLUSIONS AND CLINICAL IMPLICATIONS: The use of QP with adjuvant BCG for NMIBC mitigated debilitating BCG-associated toxicities and improved the completion rate for BCG induction therapy.
Keywords: Adjuvants, Immunologic; Non-Muscle Invasive Bladder Neoplasms; nádory močového měchýře neinvadující svalovinu; chinolony; BCG vakcína; adjuvantní chemoterapie; BCG Vaccine; lidé; aplikace intravezikální; Quinolones; Neoplasm Invasiveness; Urinary Bladder Neoplasms; Administration, Intravesical; nádory močového měchýře; adjuvancia imunologická; invazivní růst nádoru; Chemotherapy, Adjuvant; Humans